Państwo a problem sprawiedliwości społecznej - Kowalczyk, ks. Stanisław (Annales. Etyka w Życiu Gospodarczym, 2009)
Marxism accepted the notion of social justice, but realized it through liquidation of private property and violence of the totalitarian state. Liberalism and neoliberalism, in the name of maximal economic liberalism, reject the idea of social justice and postulate a minimal state. Republicanism and communitarianism accept ideas of common good and social justice. The social teaching of the Church proposes a subsidiary state which is not a protective one. Contemporary popes – Pius XI (Quadragesimo anno), John XXIII (Mater et Magistra), Paul VI (Populorum progressio), John Paul II (Sollicitudo rei socialis, Centesimus annus) – postulate participation of the state in social justice. The main of its obligations are: protection and financial aid for key sectors of economic life (including agriculture), profamily policy, fighting against unemployment and providing fair salary, limited economic intervention (while respecting the rules of the free market economy at the same time), medical and social care.